2017
DOI: 10.1245/s10434-017-5783-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status is a Predictor of Postoperative Complications After Cancer Surgery in the Very Old

Abstract: Functional status seems to be related to surgical morbidity in the very old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…We also found that poor preoperative functional capacity was associated with poor survival after colon cancer surgery, which is similar to the results of a previous study reporting that functional status seems to be related to postoperative complications, including mortality. 42 In this study, we first found that use of postoperative NSAIDs (IV tenoxicam 20 mg • day -1 for 3 days) was associated with poor survival after colon cancer surgery. By contrast, a meta-analysis showed that NSAID use (oral dosage of aspirin from 75 to greater than 300 mg daily) after diagnosis, but not prediagnosis, improved colorectal cancer survival.…”
Section: Perioperative Medicinementioning
confidence: 93%
“…We also found that poor preoperative functional capacity was associated with poor survival after colon cancer surgery, which is similar to the results of a previous study reporting that functional status seems to be related to postoperative complications, including mortality. 42 In this study, we first found that use of postoperative NSAIDs (IV tenoxicam 20 mg • day -1 for 3 days) was associated with poor survival after colon cancer surgery. By contrast, a meta-analysis showed that NSAID use (oral dosage of aspirin from 75 to greater than 300 mg daily) after diagnosis, but not prediagnosis, improved colorectal cancer survival.…”
Section: Perioperative Medicinementioning
confidence: 93%
“…25 , 26 The decreased functional status of the 80-andabove cohort compared to the under-80 cohort may have also predisposed them to preventable complications like acquisition of infection or development of pressure sores. 27 Beyond operative time, LOS and functional status may thus provide points of intervention for further risk management in elderly TSA patients. However, such interventions depend on the indication for TSA, such as the potential use of preoperative physical therapy aimed at optimizing mobility and functional independence before surgery is limited in the setting of emergent TSA for fall-related fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Такий підхід, ймовірно, може бути вигідним для пацієнтів з ожирінням у загальній хірургії, оскільки більшість із них мають багато елементів шкали RCRI (ІХС, СН, діабет), проте це вірогідно не впливає на відсоток періопераційних кардіальних ускладнень [10,11]. Гіпотеза про вагомість передопераційного дослідження функціонального стану для прогнозування ускладнень нещодавно була підтверджена в абдомінальній хірургії для пацієнтів похилого віку [12] і в хірургії шийного відділу хребта -для будь яких пацієнтів [13]. Але стосовно пацієнтів з ожирінням ми не знайшли подібних досліджень у доступній літературі.…”
Section: вступunclassified
“…Saraiva та співавт. [12] оригинальные исследования / Original Researches функціональний статус (МЕТ > 4) у них обумовлював зниження ймовірності ускладнень (СШ 0,11; 95% ДІ 0,02-0,85; p = 0,034). Аналогічні результати були отримані S.V.…”
Section: обговоренняunclassified